Cyclic Hydrazide‐Functionalized Poly(ethylene oxide) Frameworks for the Synthesis of pH‐Cleavable Drug‐Carriers and Their Applications for the Stabilization of Gold Nanoparticles. Issue 12 (14th May 2019) - Lee, Geon Chang; Seo, Donghwa; Kim, Junggyu; Siddique, Abu B.; Park, Hyeonjong; Kim, Hyun Jun; Kang, Ho‐Jung; Lee, Jae Yeol; Lim, Jeewoo; Kim, Jungahn; Kim, Sehoon
Abstract: In this paper, two different types of poly(ethylene oxide) (PEO) frameworks with different functional groups such as the thiol group and cyclic hydrazide in the α, ω ‐positions bearing "smartness" are introduced. These heterobifunctional PEOs are synthesized via different functionalization approaches using t ‐butoxy PEO. Heterobifunctional PEOs, both α‐luminol‐ω‐thiol PEO and α‐thiol‐ω‐cyclic hydrazide PEO, are prepared by chain‐end functionalization of the reactive t ‐butoxy PEOs. The chain‐end luminol as a cyclic hydrazide is found to be effective to yield pH‐responsive prodrugs from the reaction with doxorubicin (Dox) yielding corresponding Dox‐tethered PEO. The active t ‐butoxy PEO‐initiated block copolymerization of N ‐phenylmaleimide ( N ‐PMI) in acetone yields a block copolymer controlled in the 3‐ to 5‐units range of the N ‐PMI group. The deprotection of the t ‐butoxy group, followed by tosylation, thioacetylaton, and the Gabriel process, provides corresponding α‐thiol‐ω‐cyclic hydrazide PEO. The functionality yields are almost quantitative (over 98 mol%). Polymeric prodrugs such as Dox‐tethered PEO and folate‐conjugated PEO are successfully employed for the stabilization of gold (Au) nanoparticles. The resulting products are characterized by a combination of proton nuclear magnetic resonance ( 1 H NMR) spectroscopic, ultraviolet (UV)–visible spectroscopic, Fourier transform infrared (FT‐IR), transmission electron microscopic (TEM), and size‐exclusion chromatographic (SEC) analysis. Abstract : Two different types of smart poly(ethylene oxide) (PEO) frameworks with both the thiol group and cyclic hydrazide at the α, ω‐positions are introduced. Both PEOs are expected to be used as stabilizers for gold nanoparticles as drug‐nanocarriers. The functionalization yields are almost quantitative (over 98 mol%). The resulting prodrugs such as Dox‐tethered PEO and folate‐conjugated PEO are used successfully for the stabilization of gold (Au) nanoparticles.